John Salmond and Native Title in New Zealand: Developing a Crown Theory on the Treaty of Waitangi, 1910-1920 - Hickford, Mark (Victoria University of Wellington Law Review, 2008)
This extended essay argues for a new approach towards the writing of constitutional histories of the Crown within New Zealand. It looks specifically at the conceptions of the relationship between the Treaty of Waitangi, the common law and customary interests that the Crown and its legal advisors actually employed in internal deliberation and external positioning. In looking at the processes for articulating the Crown’s preferred legal position during John Salmond’s tenure as Solicitor-General, this article notes the overwhelming prevalence of statute and Treaty-based conceptions in law (as well as areas of historical change and discontinuity). Common law approaches emerged in the later twentieth century through newly minted theories or doctrines of aboriginal title but were never regarded as distinct options by the historical actors themselves. The concern of this article is with how those actors – most notably Salmond – conceived, acted upon and adapted their perception of the Crown’s constitutional obligations to Māori. In mapping the course of a Crown legal "register" or way of speaking about native title and the Treaty of Waitangi, the essay aims to reveal the rich and contested nuances of the approaches assumed by the legal advisors to the Crown on the question of the Treaty from 1910 until 1920 and its relevance to a governmental outlook on customary property.